Analisis Kandungan Kadmium (Cd) pada Sedimen di Perairan Teluk Totok, Minahasa Tenggara - Glorya Claritha Mongkau; Sri Seprianto Maddusa; Jane M.F. Tahulending (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Heavy metal contamination in coastal waters is an environmental issue that affects ecosystem balance and public health. Cadmium (Cd) is a non-essential heavy metal that is toxic, persistent, and has the potential to accumulate in aquatic sediments. This study aimed to analyze cadmium (Cd) concentrations in sediments from Totok Bay and compare the results with the applicable sediment quality standards. A quantitative descriptive design was employed using field surveys and laboratory analyses. Sediment samples were collected from 16 sampling points using a purposive sampling method at a depth of 10–15 cm. Cadmium concentrations were analyzed using the Inductively Coupled Plasma (ICP) method at the Makassar Public Health Laboratory. The results showed that cadmium concentrations in all 16 sediment samples were below the instrument detection limit (<0.00003 mg/kg). These values were far below the NOAA Sediment Quality Guidelines threshold of 36.6 mg/kg, indicating that all samples met environmental safety requirements. In conclusion, sediments in Totok Bay have not been contaminated with cadmium at levels that pose a risk to the ecosystem or public health. Nevertheless, periodic monitoring remains necessary due to ongoing mining activities in the surrounding area. This study was limited to the analysis of cadmium in sediment media only. Future studies are recommended to investigate other heavy metals and include water and aquatic biota as environmental media to support more comprehensive environmental monitoring.